The association between metabolic syndrome and major adverse cardiac and cerebrovascular events in patients with acute coronary syndrome undergoing percutaneous coronary intervention - Hosseini, Kaveh; Khalaji, Amirmohammad; Behnoush, Amir Hossein; Soleimani, Hamidreza; Mehrban, Saghar; Amirsardari, Zahra; Najafi, Kimia; Fathian Sabet, Mehrshad; Hosseini Mohammadi, Negin Sadat; Shojaei, Shayan; Masoudkabir, Farzad; Aghajani, Hassan; et al. (Scientific reports, 2024)
Metabolic syndrome (MetS) poses an additional risk for the development of coronary artery disease and major adverse cardiac and cerebrovascular events (MACCE). In this study, we investigated the association between MetS and its components and MACCE after percutaneous coronary intervention (PCI) in patients with acute coronary syndrome (ACS). The presence of MetS was calculated at baseline using the NCEP-ATP III criteria. The primary outcome was MACCE and its components were secondary outcomes. Unadjusted and adjusted Cox Regression models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CI) of the association between MetS or its components and MACCE and its components. A total of 13,459 ACS patients who underwent PCI (MetS: 7939 and non-MetS: 5520) with a mean age of 62.7 ± 11.0 years (male: 72.5%) were included and median follow-up time was 378 days. Patients with MetS had significantly higher MACCE risk (adjusted HR [aHR] 1.22, 95% CI 1.08–1.39). The only component of MACCE that exhibited a significantly higher incidence in MetS patients was myocardial infarction (aHR 1.43, 95% CI 1.15–1.76). MetS components that were significantly associated with a higher incidence of MACCE were hypertension and impaired fasting glucose. Having three MetS components did not increase MACCE (aHR 1.12, 95% CI 0.96–1.30) while having four (aHR 1.32, 95% CI 1.13–1.55) or five (aHR 1.42, 95% CI 1.15–1.75) MetS components was associated with a higher incidence of MACCE. MetS was associated with a higher risk of MACCE in ACS patients undergoing PCI. Among MACCE components, myocardial infarction was significantly higher in patients with MetS. Impaired fasting glucose and hypertension were associated with a higher risk of MACCE. Identifying these patterns can guide clinicians in choosing appropriate preventive measures.